Mitochondrial Dysfunction in Endothelial Cells: A Key Driver of Organ Disorders and Aging - Elena Grossini; Sakthipriyan Venkatesan; Mohammad Mostafa Ola Pour (Antioxidants)
Mitochondria are of great importance in cell biology since they are major sites of adenosine triphosphate (ATP) production and are widely involved in different cellular pathways involved in the response to stress. During ATP production, reactive oxygen species (ROS) can be produced. While a small amount of ROS may be important for the regulation of physiological processes, at elevated levels they can turn into harmful agents leading to cellular damage. From a pathological perspective, it could be particularly interesting to focus on mitochondrial function in endothelial cells since they may be involved in the development of aging and in the onset of different diseases, including renal, cardio-metabolic, liver and neurodegenerative ones. However, to date, there are no surveys which address the above issues. To fill this gap, it may be valuable to collect recent findings about the role of mitochondria in the regulation of endothelial function, not only to increase knowledge about it but also for clinical applications. Here, we overview the most recent knowledge about the above issues in the view of characterizing the role of mitochondria in endothelial cells as an innovative potential target for the prevention of aging, as well as the treatment of the above pathological conditions.